HPLC‐ESI‐MS/MS analysis and pharmacokinetics of luteoloside, a potential anticarcinogenic component isolated from Lonicera japonica, in beagle dogs. (2nd August 2012) - Qiu, Feng; Li, Zhaoxia; He, Lang; Wang, Dan
ABSTRACT Luteoloside is a potential anticarcinogenic component isolated from Lonicera japonica, a traditional Chinese medicine (TCM). This study details the development and validation of a sensitive and accurate HPLC‐ESI‐MS/MS method for the quantification of luteoloside in dog plasma. Sample pretreatment includes simple protein precipitation using methanol–acetonitrile (1:1, v/v). A Phenomenex Gemini C18 column (2.0 × 50 mm, i.d., 3.5 µm) was used to separate luteoloside and internal standard by gradient mode with mobile phase consisting of water containing 0.1% formic acid and methanol containing 0.1% formic acid at a flow rate of 0.40 mL/min with a column temperature of 25°C. The detection was performed by positive ion electrospray ionization (ESI) in multiple reaction monitoring mode. The calibration curves were linear (R > 0.995) over the concentration range 1.0–2000 ng/mL and the lower limit of quantification was 1.0 ng/mL. The intra‐day and inter‐day precisions (RSD) were all <15%, accuracies (RE) were within the range of ±15%, and recoveries were between 85.0 and 115%. The validated HPLC‐ESI‐MS/MS method was successfully applied to determine plasma concentrations of luteoloside after intravenous administration of luteoloside at a dose level of 20 mg/kg. Copyright © 2012 John Wiley & Sons, Ltd.